(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The environment plays a vital and important role in the life of human and their endeavors. There is scarcity of information factors that determine the behaviour of students. The research assessed the determinants of environmental responsible behavior among undergraduate students of College of Humanities and Culture, Osun State University, Osogbo, Nigeria. This research study adopted a descriptive research design, using a case study approach. Multi-stage random sampling technique was used. The sample size of 121 was obtained out of 1262 of the total numbers of students in the four randomly selected Departments. Chi-square was employed to test the significant relationship between student socio-economic characteristics and their environmental awareness and attitudes. Spearman rank correlation was also employed to test the significant correlation between environmental awareness and attitude of students. The result of the research showed that there was no significant relationship between students’ socio-economic characteristics and their environmental awareness and attitudes at p>0.05. However, the study showed that there is significant correlation between environmental awareness and attitudes of students at p<0.05. The study concluded that environmental awareness has a powerful impact on environmental attitude and behaviour of the students, hence, recommends that environmental studies, degradation and conservation should be incorporated into student’s curriculum to improve their positive attitudes towards the environment.